1968
DOI: 10.1002/pssb.19680260103
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electric properties of Cu2S single crystals

Abstract: Single crystals of p-Cu,S are obtained with a hole concentration of 7.4~10'*cm-~, a mobility of 25 cmp V-ls-l, and a thermoelectric power of 90 mV/deg. The electrical conductivity, thermoelectric power and Hall effect are measured between 20 and 000 OC. A jump due to structural transformetions is observed in the temperature dependence of these parameters at 125 and 480 O C . The activation energy is found to have a value of 1.8 eV for the intrinsic range of the Conductivity, the value found for the extrinsic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…This should be attributed to the band flattening with increasing the superionicity and level of Cu disorder . Similar change in m * has also been observed in Cu 2 S when Cu 2 S transfers from low‐superionicity cha‐rt phase into partial‐superionic cha‐ht phase (Figure b) …”
Section: Relationship Between Superionicity and Performancesupporting
confidence: 71%
See 1 more Smart Citation
“…This should be attributed to the band flattening with increasing the superionicity and level of Cu disorder . Similar change in m * has also been observed in Cu 2 S when Cu 2 S transfers from low‐superionicity cha‐rt phase into partial‐superionic cha‐ht phase (Figure b) …”
Section: Relationship Between Superionicity and Performancesupporting
confidence: 71%
“…[191] Similar change in m* has also been observed in Cu 2 S when Cu 2 S transfers from lowsuperionicity cha-rt phase into partial-superionic cha-ht phase (Figure 7b). [179,[193][194][195] Adv. Mater.…”
Section: Temperature-dependent Carrier Transport Propertiesmentioning
confidence: 99%
“…high-frequency method (9.3 GHz), while the measurements in [4] are based on a static method. Above 403 K we did not detect, within the experimental error, any changes in the EPR line intensity and this fact is consistent with the data of[4]. As…”
supporting
confidence: 92%
“…Scientists in eastern Europe apparently started to study the TE properties of Cu 2 S in the middle of the 1960s . Abdullaev et al reported Seebeck coefficients ( S ) between 100 and 200 μV K −1 in the α phase, about 300 μV K −1 in the β phase, and up to 960 μV K −1 in the γ phase (at 670 °C) . As far as resistivity ( ρ ) is concerned, the values measured by this team were about 2 mΩ cm for both the α and the β phase.…”
Section: The (Long) History Of Copper Sulfides/selenides As Thermoelementioning
confidence: 91%